Dukungan Keluarga Pada Pelaksanaan Mobilisasi Dini Pasien Pasca Stroke Iskemik - Diny Vellyana; Asri Rahmawati (HB PRESS, 2021)
Rehabilitation programs are needed to minimize the disabilities caused after a stroke, one part of rehabilitation is early mobilization. Early mobilzation is needed to prevent and limit anxiety and depression,prevent thrombolism, reduce morbidity and improve cardiovascular function and reduce recurrence rates in patients. The purpose of this study was to determine the relationship between family support and early mobilization in post – stroke patients at the Pringsewu Regional General Hospital.In this study, the authors used a cross – sectional method to determine whether there was a relationship between nurse knowledge and early mobilization management in post – stroke patients. The population in this study were 24 patients in the nursing room of the Pringsewu Regional General Hospital with a medical diagnosis of ischmemic stroke and total sampling techniques.Based on the results of the analysis, it is known that there is a relationship between family support and the implementation of early mobilization in post – stroke patients at Pringsewu Hospital,the results of statistical test with chi square (X2) obtained p – value = 0.007 <? = 0.05 and 73.3% of respondents get family support in the post – stroke mobilization process. Family support is able to make the family function again, including in improving health status, therefore the family support process should be considered by nurse in the process of providing nursing care.